Verification of autoclaving-cooling treatment to increase the resistant starch contents in food starches based on meta-analysis result - Faridah, Didah Nur; Silitonga, Rhoito Frista; Indrasti, Dias; Afandi, Frendy Ahmad; Jayanegara, Anuraga; Anugerah, Maria Putri (Frontiers in Nutrition, 2022)
Autoclaving-cooling is a common starch modification method to increase the resistant starch (RS) content. The effect of this method varies depending on the type of crop and treatment condition used. The objectives of this study were to verify the autoclaving-cooling treatment based on a meta-analysis result and to evaluate the physicochemical properties of modified starches. The meta-analysis study used 10 articles from a total of 1,293 that were retrieved using the PRISMA approach. Meta-analysis showed that the optimal treatments of autoclaving-cooling process that increase the RS content significantly, was in starch samples from the cereal group (corn, oats, rice) (SMD: 19.60; 95% CI: 9.56 – 29.64; p < 0.001), with water ratio 1:4 (SMD: 13.69; 95% CI: 5.50 – 21.87; p < 0.001), using two cycles of autoclaving-cooling (SMD: 16.33; 95% CI: 6.98 – 25.67; p < 0.001) and 30 minutes of autoclaving heating (SMD: 12.97; 95% CI: 1.97 – 23.97; p < 0.001) at 121 °C (SMD: 12.18; 95% CI: 1.88 – 22.47; p < 0.001). Verification using corn flour and corn starch showed a significant increase in RS contents from 15.84% to 27.78% and from 15.27% to 32.53%, respectively, and a significant decrease in starch digestibility from 67.02% to 35.74% and from 76.15% to 28.09%, respectively. Treated sample also showed the pasting profile that was stable under heating and stirring.